ACADEMIC REDESIGN: ACCOMPLISHING MORE WITH LESS - Graves, William H. (Online Learning, 2004)
Community colleges are under persistent pressure to spend more on technology. In lieu of bolting technology onto essential academic and administrative process at additional net cost, savvy community college leaders are planning and implementing academic service redesign strategies to achieve measurable outcomes constituting gains in academic productivity. This paper presents case studies of four higher education institutions that contracted with Collegis for a range of planning, marketing, student recruiting, academic, and technology management and support services. To be able to accomplish more with less, three strategies are discussed: (1) redesigning individual course sections to increase learning and convenience, (2) redesigning common courses to decrease costs and increase learning outcomes, and (3) redesigning program delivery to participate in flex markets.